Evidence for circulating cancer stem-like cells and epithelial–mesenchymal transition phenotype in the pleurospheres derived from lung adenocarcinoma using liquid biopsy. Issue 3 (March 2017) - Mirza, Sheefa; Jain, Nayan; Rawal, Rakesh
Lung cancer stem cells are supposed to be the main drivers of tumor initiation, maintenance, drug resistance, and relapse of the disease. Hence, identification of the cellular and molecular aspects of these cells is a prerequisite for targeted therapy of lung cancer. Currently, analysis of circulating tumor cells has the potential to become the main diagnostic technique to monitor disease progression or therapeutic response as it is non-invasive. However, accurate detection of circulating tumor cells has remained a challenge, as epithelial cell markers used so far are not always trustworthy for detecting circulating tumor cells, especially during epithelial–mesenchymal transition. As cancer stem cells are the only culprit to initiate metastatic tumors, our aim was to isolate and characterize circulating tumor stem cells rather than circulating tumor cells from the peripheral blood of NSCLC adenocarcinoma as limited data are available addressing the gene expression profiling of lung cancer stem cells. Here, we reveal that CD44(+)/CD24(−) population in circulation not only exhibit stem cell–related genes but also possess epithelial–mesenchymal transition characteristics. In conclusion, the use of one or more cancer stem cell markers along with epithelial, mesenchymal and epithelial mesenchymal transition markers will prospectively provide the most precise assessment of the threat for recurrence and metastatic disease and has a great potential for forthcoming applications in harvesting circulating tumor stem cells and their downstream applications. Our results will aid in developing diagnostic and prognostic modalities and personalized treatment regimens like dendritic cell–based immunotherapy that can be utilized for targeting and eliminating circulating tumor stem cells, to significantly reduce the possibility of relapse and improve clinical outcomes.